METHODS OF DA'WAH IN QURAN AND HADITH: A COMPARATIVE ANALYSIS ACROSS ERAS - Septiani, Nurul (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The methods of Da’wah (Islamic proselytization) have undergone significant transformations from the classical period to the present digital era. This study explores how the Quran and Hadith serve as foundational sources for Da’wah practices, highlighting the evolving interpretive frameworks that shape these methods across different periods in Indonesian Islam. Using a qualitative descriptive approach, this research delves into the roles and challenges that Quranic exegesis and Hadith interpretations have played in developing Da’wah methods. The study examines classical, modern, and digital-era Da’wah methods, analyzing their alignment with Islamic teachings, with particular emphasis on the differences in interpretive approaches by various scholars. The findings underscore the continued relevance of traditional methods such as verbal (bil lisan) Da’wah, practical (bil hal) Da’wah, and wisdom-based (bil hikmah) Da’wah, while also exploring the profound impact of social media and digital platforms on contemporary proselytization efforts. This research contributes to the literature on Islamic Da’wah methods in Indonesia, proposing that, despite the evolution of da’wah methods, the core principles of wisdom, good counsel, and exemplary behavior remain central to effective Da’wah. The study also provides insights into the opportunities and challenges digital da’wah presents, emphasizing the need for a balanced approach in leveraging new platforms while maintaining the integrity of the message.